Update on the Engineering Design Studies Evaluated in the NRC Report Analysis of Engineering Design Studies for Demilitarization of Assembled Chemical Weapons at Pueblo Chemical Depot - National Research Council (U.S.). Committee on Review and Evaluation of Alternative Technologies for Demilitarization of Assembled Chemical Weapons: Phase II (National Academies Press, 2002)
Letter report containing several engineering design tests which had not been completed in time to be included in the earlier related report titled: Analysis of engineering design studies for demilitarization of assembled chemical weapons at Pueblo Chemical Depot.
Keywords: Chemical weapons disposal : Colorado : Pueblo; Engineering design; Electronic books